PERANCANGAN PRODUK ALAT BANTU CLOSET JONGKOK - Soenandi, Iwan Aang; Malvin, Raymond (Teknik dan Ilmu Komputer, 2013)
Toiletor water closet is ahome furnishingwhich sole purposeis a place for sewage, urine andfeces. Based onvalidity andreliability test,the use ofsquatting closetfor a long periodcan causeleg pain, cramps, tinglingpainin weaklegand knee pain. There are various products and designs of flush toilets which are not suitable for middle to low income people as the price is higher than the squatting closet. The research findings suggested that many people did not have flush toilets at home. It is therefore important to design a prototype to address the problem of squatting closet. The prototype design was in accordance with the respondentsâ data based on ergonomics and anthropometric science. The design includes a 20cm high backrest, 37cm seat width, 42cm seat length, 41cm backrest width, and 43cm seat height. Â Keywords: validity and realibility test, prototype,anthropometric, ergonomics